Demographic, Clinicopathological and Laboratory Features of Focal Segmental Glomerulosclerosis Patients - Tuba Elif Özler; Özge Can Ceylan; Egemen Cebeci; Sami Uzun; Serhat Karadağ; Oktay Özkan; Yağmur Başhan; Hatice Burcu Dağ; Zeynep Karaali; Savaş Öztürk (Haseki Tıp Bülteni, 2020)

(untitled)
Aim:Focal segmental glomerulosclerosis (FSGS) is one of the common glomerulonephritis in Turkey and the world. The aim of our study was to determine demographic and clinical features and biopsy results of patients who were followed up with primary FSGS in our center.Methods:Ninety-nine adult patients with FSGS diagnosed via renal biopsy, who were followed up in our outpatient clinic, were included in our single-center, retrospective, cross-sectional study. Patients with secondary FSGS were excluded. Demographic and clinical features and biopsy results were examined retrospectively.Results:Fifty-nine patients (59.6%) were women. Nephrotic syndrome was the most common biopsy indication (68.7%) and the mean estimated glomerular filtration rate at presentation was 78.9±35.8 mL/min/1.73 m2. The mean serum albumin level was 3.2±0.9 g/dL and urine protein level was 3485 mg/day (interquartile range: 1739-7275). Interstitial fibrosis was detected in 63.4% and tubular atrophy in 74.7% of patients.Conclusion:The complaints and clinical data of our patients with FSGS were similar with the country and world data. Approximately 40% of the patients presented with decreased renal functions at the time of biopsy. Biopsy should be considered earlier in patients suspected of FSGS, as tubular atrophy and interstitial fibrosis rates were high in biopsies.